Ultrahigh resolution spectroscopy for dimethyl sulfide at the ν1- and ν8-bands by a distributed feedback interband cascade laser. (May 2020) - Wang, Zehua; Wang, Ruixue; Li, Jinyi; Yan, Yue; Du, Zhenhui
Highlights: Ultrahigh resolution (5.69 × 10-6 cm −1 ) achieved. Dimethyl sulfide absorption cross-sections have been determined with an estimated uncertainty of 0.43%. Using the advantages of a White-cell and distributed feedback interband cascade laser. Providing an accurate basis for dimethyl sulfide remote sensing and absolute spectral measurement applications. Abstract: The ultrahigh-resolution, air-broadened mid-infrared absorption spectrum of dimethyl sulfide (DMS) was recorded in the spectral region of 2994.17–2999.03 cm −1, where the strong ν 1 -/ ν 8 -bands are located. Benefitting from the tunable laser absorption spectrometry with a distributed feedback interband cascade laser, the spectral resolution achieved 5.69 × 10 −6  cm −1 . The recorded spectra of DMS are very close to that in the Pacific Northwest National Laboratory (PNNL) database, however it has a much lower absorbance uncertainty of 0.38%. And the maximum relative difference of the full width at half maximum and the integrated area of spectral peaks between the recorded spectra and the PNNL data are as large as 16.7% and 27.9%, respectively, which could mainly come from the difference of the spectral resolution. The more accurate reference spectrum is hopeful to be applied to absolute measurement and remote sensing for gaseous DMS.